Interaction of Nature and Culture - Gendrolis, Edmundas (Problemos, 1990)
In the paper the interaction between nature and culture is analysed in the aspects of appropriative and productive economy. Special attention is paid to the impact of natural environmental factors upon the development of society as a whole and to the particular changes in the way of production in the particular regions. Finally, the theory of linear development of culture is criticised and the impacts of the reconstructive activity of man upon the environment are analysed.